Factors Associated with Cutting Errors During Halal Broiler Slaughtering in Samarinda, Indonesia - Ari Wibowo; Suhardi Suhardi; Manat Chaijan; Zuraida Hanum (Jurnal Agripet, 2026)
This study evaluated the effectiveness of training in reducing processing defects (cutting errors) in poultry production. The research was conducted in Samarinda City, Indonesia (Districts of North Samarinda, South Samarinda, Samarinda Kota, Samarinda Ulu, and Sungai Pinang) from October to November 2024. A quantitative survey design was used. The sample consisted of 50 slaughter workers selected through purposive sampling, with the criteria requiring active employment and a minimum of one year of slaughtering experience. Data were collected using a structured questionnaire with three sections (demographics, slaughter technique comprehension/skills, and a standardized operational observation protocol) to evaluate the completeness of severance of the trachea, esophagus, and major blood vessels in the neck region. Statistical analyses included independent samples t-tests, correlations, and regression modeling. The t-test results indicate a statistically significant disparity in the miss-cut rates between trained and untrained workers (t = 13.198, p < 0.05, critical t = 2.0106), demonstrating that training significantly improves cutting accuracy. Regression analysis revealed that the model accounted for 45.6% of the variance in miss-cut occurrences (R2 = 0.456). Notably, training emerged as the sole significant predictor, with a negative coefficient (β = -0.4201, p < 0.05), suggesting that it directly reduces errors. In contrast, variables such as work experience had no statistically significant influence. These findings underscore the critical role of targeted training programs in mitigating processing defects and provide actionable insights for quality control in poultry processing operations.